Determinan Implementasi Standar Akuntansi Pemerintahan (SAP) Berbasis Akrual: Studi pada Badan Penegelola Keuangan dan Aset Daerah (BPKAD) Kota Jambi dan Kabupaten Tanjung Jabung Barat - Nurhasniwati; Mukhzarudfa; Enggar Diah PA (Magister Ilmu Akuntansi Universitas Jambi, 2020)
This study aims to examine the factors that influence the implementation of government accounting standards, namely human resources, infrastructure and information technology in BPKAD Jambi City and Tanjung Jabung Barat District. This research is a survey research by distributing questionnaires directly to the sample as primary data. The sample technique used is purposive sampling. The sample in this study was the Head of Subdivision of Finance and Budget Users in BPKAD Jambi City and Tanjung Jabung Barat Regency. The analytical method used is multiple linear regression using the SPSS 24 application. The results of this study indicate that human resources, infrastructure and information technology simultaneously influence the implementation of accrual-based government accounting standards. Human resources and information technology affect the implementation of accrual-based government accounting standards. Infrastructure has no effect on the implementation of accrual-based government accounting standards. The magnitude of the influence of human resources, infrastructure and information technology with the implementation of accrual-based SAP of 64.9%, while the remaining 35.1% is influenced or explained by other variables not included in this research model. So that it can be stated to have a very strong closeness coefficient.